Representasi Budaya Indonesia dalam Buku Teks Bahasa Inggris Sekolah Dasar: Analisis Wacana Kritis. - Fathiyya, Iftikharunnisa'; Mobit, Mobit; Wahyuna, Yuna Tresna (Peneliti.net, 2024)
Textbooks are one of the most important media in the English teaching-learning process. It plays a critical role for students and teachers in easing the teaching and learning processes. Using textbooks, teaching and learning processes are expected to run better, because teachers and students are facilitated in building an understanding of the ongoing material. Many subjects are presented in textbooks, such as small things done in daily life, food, movies, or culture from within and outside the country. This research aims to investigate Indonesian culture presented in the sixth-grade elementary English textbook entitled